Development of salt substitute for reduction of sodium in ready to eat mushroom soup and snack foods - Mahannopkul, Wannadee; Yossaksri, Janchay (Bulletin of Applied Sciences, 2022)
The development of sodium-replacement salts or salt substitutes in this research was produced by reduced size of sodium salt (NaCl) to very small particles, 45 micron. Salt substitutes was prepared by mixing NaCl and KCI at the ratio 1:1, 1:2 and 2:1 (by weight). Sensory evaluation of salt substitute solution was conducted using Triangle test with 20 panelists and statistical tested by Chi-Square (X2). The sample of salt substitute solution test at the concentration 1% by weight, panelist could not detect the difference between control sample (Sodium salt) and salt substitute (NaCl and KCl ratio 1:1). Sensory evaluation result for the concentration 2% solution, panelist could not detect the difference between control sample and salt substitute (NaCl and KCl ratio 1:1 and 2:1), at the 95 percent confidence level (P>0.05). The sensory evaluation result shown that panelist can detect the difference of control sample and salt substitute NaCl and KCl at the ratio 1:2 (P<0.05) The formula development of salt substitute contained KCl and NaCl at the ratio 60:40, 65:35 and 70:30, added taurine 1%, tartaric acid 0.1% or ascorbic acid 0.1%. These salt substitutes formulas were analyzed sodium content, it has sodium 15.01-17.59 gram/100 gram. Suitable salt substitute formula contained KCl and NaCl at the ratio 65:35 added taurine 1% and ascorbic acid 0.1%, it used for Straw mushroom soup and product has sodium 32.38-35.97 milligram/one serving (150 gram), which complied with definition of very low sodium food. Salt substitute formula was tested in snack, which contained of KCl and NaCl ratio 65:35, added taurine 1%, ascorbic acid 0.1% and mix with dried seaweed. This sodium-replacement salts was used for flavoring on banana cracker. Salt substitute mixed with dried seaweed contained K 65.58 gram, Na 9.09 gram and NaCl 86.85 gram. The flavoring banana cracker with salt substitute (mixed with dried seaweed) has sodium content 131.20 mg of sodium per serving (100 gram), which complied with definition of low sodium food.